Designing Performance Appraisal to Improve Employee Performance - Isyraqi Reza, Leo Vickozy; Rahmatsyah Putranto, Nur Arief (Journal of Business and Management, 2019)
Coffee consumption is growing fast among Indonesian market throughout the period of 2016-2021 is predicted to grow an average of 8.22% / year. Kozi Budara is one of place that serve Indonesian Coffee. Since Kozi Budara operate in service industry, employee is vital part to retain quality of service. Kozi Budara experiencing declining of employee performance for past month. This problem happen because of bias judgement when owner appraising employee. This study aims to design ideal performance appraisal system to increase employee performance. Graphic rating scale method will be used in this study. To design ideal performance appraisal, this research analyzed job analysis to standardize the employee performance. Job analysis will be used to design graphic rating scale based on Kozi Budara condition to decrease bias judgement when appraising employee.Keywords : Appraisal methods, Employee performance, Human resource management, Performance appraisal, Performance management, Work design